KEANEKARAGAMAN JENIS BURUNG DI KAWASAN HUTAN LINDUNG GUNUNG SIRIMAU - John F. Sahusilawane (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2017)
This study was conducted to determine the composition of bird diversity and vegetation stages and composition, to determine the variables that most influence the diversity of birds in protected forests Sirimau, This study was conducted for three months from September 2015 to November 2015. Bird observations and habitat variables performed using the Point Count method, and found thirty observation points at each location, with 30 cm trellis and 200 m plot distance. The analysis of birds and vegetation in Sirimau mountain forests shows that, bird species are dominated by Red Eye (Aplonis Motalica), and more than 50 species of vegetation exist in the research location, dominated by fruits.